Simulation as a decision support tool in maintenance float systems: System availability versus total maintenance cost - Pereira, Guilherme (2011)
This paper is concerned with the use of simulation as a decision support tool in maintenance systems, specifically in MFS (Maintenance Float Systems). For this purpose and due to its high complexity, in this paper the authors explore and present a possible way to construct a MFS model using Arena® simulation language, where some of the most common performance measures are identified, calculated and analysed. Nevertheless this paper would concentrate on the two most important performance measures in maintenance systems – system availability and maintenance total cost. As far as these two indicators are concerned, it was then quite clear that they assumed different behavior patterns, specially when using extreme values for periodic overhauls rates. In this respect, system availability proved to be a more sensitive parameter.